ENVIRONMENTAL ACCOUNTING: ENERGY EFFICIENCY, RENEWABLE ENERGY, AND CIRCULAR ECONOMY - Gadang Wardono; Noviandy; Fajar Fathoni; Wiwit Afrigus (International Journal of Contemporary Accounting, 2023)
This article evaluates waste management in supporting energy efficiency, utilization of new and renewable energy (NRE), and circular economy as part of environmental accounting. The research used a case study on a community empowerment program by one of the cement companies in Indonesia, PT Indocement Tunggal Prakarsa Tbk (ITP). Interviews were conducted with 16 administrators and workers of community empowerment program, which manages the company's waste management, along with observation on the program implementation. This study analyzed information on the new renewable energy (NRE) from treated waste, circular economy processes through the stages of waste management, economic and environmental impacts, as well as supporting facilities and infrastructure in the waste management process. The results of the study found that the use of multilayer waste can minimize the environmental impact caused by the company in the coal burning process. Until February 2023, the multilayer waste or refused derived fuel (RDF) used by the community empowerment group has replaced coal by 0.04% at the Citeureup ITP Plant. The use of multilayer waste as an NRE managed to reduce CO2 emissions in the combustion process of cement production. The increase in income from waste processing reached 469.30% from the sales of segregated waste, compost, RDF, and services. The waste management program has improved the community's quality of life in terms of increased knowledge, skills, and economy of its members, as well as the creation of a circular economy in the community. This empirical research used a case study of an Indonesian cement company that has been able to calculate its energy efficiency, which is one of the applications of environmental accounting.